2023
DOI: 10.1002/hcs2.65
|View full text |Cite
|
Sign up to set email alerts
|

Financial burden of seeking diabetes mellitus care in India: Evidence from a Nationally Representative Sample Survey

Mehak Nanda,
Rajesh Sharma

Abstract: BackgroundDiabetes mellitus (DM) is a major public health concern in India, and entails a severe burden in terms of disability, death, and economic cost. This study examined the out‐of‐pocket health expenditure (OOPE) and financial burden associated with DM care in India.MethodsThe study used data from the latest round of the National Sample Survey on health, which covered 555,115 individuals from 113,823 households in India. In the present study, data of 1216 individuals who sought inpatient treatment and 652… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
(96 reference statements)
0
2
0
Order By: Relevance
“…We found that utilization of health care services from private health facilities puts an exorbitant burden on households in concordance with previous studies. 31,33,34,53,54,75 We also found deleterious effect of utilizing private health facilities across all states/UTs. However, the burden was more pronounced in poorer states such as Chhattisgarh, Uttar Pradesh, Madhya Pradesh, Manipur, Odisha, and Bihar, where more than 50 percent of households faced CHE incidence and over 20 percent of households were pushed below the poverty line due to seeking care from private health care facilities in the case of both inpatient and outpatient care.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…We found that utilization of health care services from private health facilities puts an exorbitant burden on households in concordance with previous studies. 31,33,34,53,54,75 We also found deleterious effect of utilizing private health facilities across all states/UTs. However, the burden was more pronounced in poorer states such as Chhattisgarh, Uttar Pradesh, Madhya Pradesh, Manipur, Odisha, and Bihar, where more than 50 percent of households faced CHE incidence and over 20 percent of households were pushed below the poverty line due to seeking care from private health care facilities in the case of both inpatient and outpatient care.…”
Section: Discussionmentioning
confidence: 58%
“…3234,38,41 Moreover, much of the noncommunicable diseases care is provided by the private health care sector in India. 33,34,41,53,7375 Previous studies have also suggested that wealthier states invest more in health, have a vast provision of private health care services, 40,76–78 and their residents usually have more financial resources to spend on health care. 47,79 On the other hand, the outpatient services were heavily concentrated among private health care providers (approximately 70%) in India, as well as across most states.…”
Section: Discussionmentioning
confidence: 99%